EFEK EKSTRAK ETANOL RIMPANG TEMUGIRING (Curcuma heyneana val) TERHADAP KADAR TRIGLISERIDA - Wahyu Widyaningsih (Pharmaciana, 2011)
The study of effect ethanolic extract Curcuma heyneana rhizoma as antihypertrigliserida examine of rats after given by dietary of high fat has been carried out. This experiment use 28 white male Wistar grooved rats with weight about 150-200 gram body weight, at about 2 -3 months old. They were divided into seven group randomly and each group 4 rats. The first group was given by standart treatment of dietary (BR II) and aquadest, the second group was given by dietary of high fatty and aquadest, the third group was given by CMC Na solution, the fourth was given by gemfibrosil in CMC Na suspension, the fifth group, the sixth group and the seventh were orally given by of ethanolic extract with dose 10g/kgBW; 20 g/kgBW; and 40 g/kgBW. Hyperlipidemia was treated with higth dietary fatty (5 gram fat cows and 10 gram egg yolk) at the second period (two weeks). The treatment of ethanolic extract Curcuma heyneana rhizoma was given after hyperlipidemia. The trigliserida content determined with GPO (Glycerol-3-Phosphate Oxidase) test. The trigliserida level in the serum analyzed on the before treatment, during the treatment and after treatment. The result of the research showed that ethanolic extract Curcuma heyneana rhizoma 2 weeks can decrease trigliserida level.